Flavonoids of Rosa rugosa Thunb. inhibit tumor proliferation and metastasis in human hepatocellular carcinoma HepG2 cells - Zhiguo Zhang (KeAi Communications Co., Ltd., 2022)
Rosa rugosa Thunb. is recognized as both medicine and edible in China. The article investigated the antitumor activity of rose flavonoids. Water-extracted rose flavonoids (RFW) and ethanol-extracted rose flavonoids (RFE) were achieved by extracting with distilled water and 70% ethanol, respectively. The effects of the two extracts on proliferation inhibition, apoptosis inducement and metastasis prevention of human HepG2 hepatocellular carcinoma cell lines were tested, via optical/fluorescence microscopy, MTT detection, Transwell assay, flow cytometry and Western blot, etc. The results indicated that rose flavonoids at low concentration (10–40 μg/mL) had a better inhibitory effect on migration and invasion of HepG2 cells in a dose-dependent manner, while rose flavonoids at high concentration (80–160 μg/mL) could induce apoptosis of HepG2 cells by up-regulating the expression of pro-apoptotic proteins p53 and Bax, and down-regulating the expression of anti-apoptotic proteins Bcl-2, leading to the functioning of caspase-3 and caspase-9. The effect of RFE at the same concentration was significantly better than that of RFW. Conclusion, this study found that rose flavonoids had a certain inhibitory effect on proliferation and metastasis of human liver cancer cells HepG2, indicating the application of rose flavonoids in preventing and treating of liver cancer.